Editorial [Hot Topic: GPCR High Throughput Screening (Part 1) (Guest Editors: David P. Siderovski and Francis S. Willard)] - Willard, Francis S.; Siderovski, David P. (Combinatorial Chemistry & High Throughput Screening, 2008)
Continuing for many decades, and even into this post-genomic era, the G protein-coupled receptors (GPCRs) remain attractive targets for the discovery of small molecule therapeutics and still constitute the largest single fraction of the “druggable proteome”, with GPCR-targeted drugs having annual sales in the tens of billions of dollars worldwide [1,2]. Further exploitation of this rich treasure trove of targets, however, demands adding novel, creative approaches of identifying GPCR signaling modulators to the continued application of traditional high-throughput screening and medicinal chemistry efforts. In two special issues of CCHTS, we have compiled accounts from a cross-section of strategies in the hopes of illuminating the breadth of available and emerging approaches to identifying small molecules that modulate GPCR signal transduction in valuable ways. In this issue (CCHTS Vol. 11, No. 5), Kenakin considers the emerging realm of allosteric modulators of GPCR signaling and the attendent modifications to screening strategies required to maximize their discovery in high-throughput screens of biological function. The number of such HTS-amenable biological readouts of GPCR action are ever-expanding; Crouch and Osmond discuss the use of labelled antibody monitoring of ERK phosphorylation status in this context, whereas Fang and coworkers consider the emerging realm of label-free, intact cell readouts. Johnston and colleagues review their work in identifying novel phage display peptides with nucleotide-state-selective affinity for heterotrimeric G-protein alpha subunits, as well as applying them in developing non-radioactive assays of G-protein activation by GPCR signaling. Smrcka and coworkers review their work in identifying novel phage display peptides with affinity for heterotrimeric G-protein beta/gamma subunits and their application to in silico compound screening for Gbeta/gamma inhibitors. Finally, Kimple et al. round out this collection of articles with the most speculative assay development concept, involving a target considerably distant from the orthosteric binding site of GPCRs - namely, the interaction of heterotrimeric G-protein alpha subunits with the GoLoco motifs of G-protein signaling regulators LGN and RGS12. In the next issue (CCHTS Vol. 11, No. 6), Houston and colleagues describe a tour-de-force application of iterative chemical synthesis and biological testing towards the rational design of ligand tools (antagonists, agonists, radioligands) for a single GPCR – the purinergic P2Y1 receptor that represents an important therapeutic target in platelet aggregation. Jensen and Roth describe a converse, post-genomics approach of screening single molecules against a multitude of receptors, and the consequent surprises and biological insights that can result from such screening. As a unique means to identify new GPCR-binding compounds in an unbiased fashion, Whitehurst and Annis describe the use of affinity selection-mass spectrometry (AS-MS) as applied to HTS of GPCRs. This newly-emergent technique relies on obtaining quantities of purified (and functional) receptor; the multitude of strategies for this technical hurdle are enumerated in encyclopedic detail in the following paper by Chiu and colleagues. In addition to enabling AS-MS and structural biology pursuits, purified GPCR preparations should also greatly facilitate antibody generation; the use of state-selective anti-GPCR antibodies in HTS and drug development is considered in the paper by Gupta and co-workers. We thank all the authors who participated in this project for their creative inputs. We hope that, in the aggregate, these articles spark renewed excitement towards GPCR signaling as a drug discovery platform and also highlight some of the novel and innovative approaches yet to be fully explored in this tried-and-true field. REFERENCES [1] Overington, J.P.; Al-Lazikani, B.; Hopkins, A.L. Nat. Rev. Drug Discov., 2006, 5, 993-6. [2] Jacoby, E.; Bouhelal, R.; Gerspacher, M.; Seuwen, K. ChemMedChem, 2006, 1, 761-82.